Xinmailong Modulates Platelet Function and Inhibits Thrombus Formation via the Platelet αIIbβ3-Mediated Signaling Pathway - Wang, Huawei; Ye, Yujia; Wan, Wen; Wang, Luqiao; Li, Ruijie; Li, Longjun; Yang, Lihong; Yang, Lai; Gu, Yajuan; Dong, Ling; Meng, Zhaohui (Frontiers in Pharmacology, 2019)
Background: Xinmailong (XML), a bioactive composite extracted from Periplaneta americana, has been widely used to treat cardiovascular diseases such as congestive heart failure. However, it is unclear whether XML has antiplatelet and antithrombotic effects. Mathods: The effects of XML on agonist-induced platelet aggregation, adhesion and spreading, granule secretion, integrin α II bβ3 activation, and thrombus formation were evaluated. Phosphorylation of Syk, PLCγ2, Akt, GSK3β, and MAPK signaling molecules was also studied on agonist-induced platelets. In addition, the antithrombotic effects of XML were observed in vivo using an acute pulmonary thrombosis mouse model. Results: XML dose-dependently inhibited in vitro platelet aggregation and granule secretion induced by thrombin, collagen, and arachidonic acid (AA). XML also greatly reduced platelet adhesion and spreading on both collagen- and fibrinogen-coated surfaces. Biochemical analysis revealed that XML inhibited thrombin-, collagen- and AA-induced phosphorylation of Syk, PLCγ2, Akt, GSK3β and MAPK. Additionally, XML significantly inhibited in vivo thrombus formation in a collagen-epinephrine-induced acute pulmonary thrombosis mouse model. Conculsions and general significance: Here, we provide the first report showing that XML inhibits platelet function and that it possesses antithrombotic activity. This suggests that XML could be a potential therapeutic candidate to prevent or treat platelet-related cardiovascular diseases.